Regulation vs deregulation of the internet: an insight into the internet watch foundation in the United Kingdom - Nazli, Ismail @ Nawang (2013)
The internet provides a new platform for communication and it has greatly affected all spheres of our daily lives. Due to its borderless nature and geographical independence, there are numerous arguments on the regulability of the internet. The debate was for the most part centred around two opposite schools of thought; cyber-libertarians and cyber-paternalists. The former believed that the internet could not be governed by any legal controls whilst the latter argued that new models and sources of rules in the form of network architecture and contractual arrangements with the internet service providers ('ISPs') would be able to enforce regulations and controls in the cyberspace. In relation to this, the United Kingdom ('UK') internet industry has taken the initial step to combat the problem of online child pornography and other illegal materials by establishing the internet watch foundation ('the IWF'). Thus, this article seeks to investigate the style of regulatory regime and the legal approach that has been adopted to govern the internet in the UK